Tindak Pidana Pelanggaran Lalu Lintas dan Upaya Penanggulangannya pada Masa Pandemi Covid-19 - I Gede Krisna; I Nyoman Gede Sugiarta; I Nyoman Subamiya (Warmadewa Press, 2021)
Traffic as a process that occurs on the highway, where its existence has a very important and central role in society, so it cannot be denied that its existence is one of the needs of the community in the form of a means to fulfill mobilization activities to meet every basic need. Traffic violations often occur and cause mobilization to be disrupted, hence the need for criminal acts for people who do not obey traffic rules. The method used in this research is an empirical, which is to study about the applicable laws and regulations by relating the issues discussed. The primary data collection technique was carried out by conducting interviews with members of the Police in the field of traffic violations at the Gianyar Regional Police. The results shows that the factors causing traffic violations were substantial factors, structure, and culture from the community. Efforts to overcome this include enforcing patrols, placing guard posts, arranging them, and socializing them to the public.